Authority and Autonomy: Paradoxes of Modern Knowledge Work - Susanne Ekman (Copenhagen Business School (CBS), 2010)
The thesis is a thorough empirical study of discourses, fantasies, and patterns of interaction in highinvolvement knowledge work. My interest in the issue was sparked by a fascination with the intensity and contradictory nature of working life for many high-skilled workers. I was curious about the ambiguities and paradoxes existing within the same dynamic, and I was puzzled by the fact that such tension-ridden and precarious machinery could keep functioning despite its constant episodes of breakdown – be they emotional or organizational. My intention was to find a gaze and a language which could capture these ambiguities and tensions, rather than insisting on classical dualisms such as profit versus meaning, instrumentality versus authenticity, power versus freedom, and influence versus vulnerability......
hdl:10398/8061
Keywords: 650